Controversies in Managing of Thoracic-Lumbar Upper Burst Fractures - Sahat Edison Sitorus (Neurologico Spinale Medico Chirurgico, 2018)
Upper burst fracture of Th12-L1 has unique anatomy because it contains lower spinal cord, medullary cone, and diaphragm which separates between the thoracic and lumbar spine. The presence or absence of neurologic deficit is the single most important factor in the decision making. The presence of profound but incomplete neural deficit in association with canal compromise represents an urgent indication of surgical decompression. Antero-lateral direct decompression with trans-thoracic trans-pleural– retroperitoneal approach given the proximity the cord and conus is the most effective method, with inter-vertebral instrumentation with or without lateral fixation or posterior instrumentation.